Investigation of beliefs relating to weight gain prevention behaviours and weight related constructs in first year female students at three South African Universities - Lasker, Gabrielle Lana (Division of Human Nutrition, 2021)
Introduction International as well as South African research indicates that first year female students at tertiary institutions may be specifically prone to weight gain and that these students should be targeted for weight management interventions. To contribute to this field of research a self-help weight management manual was developed for South African first year female students and tested in a controlled trial. The manual was found to result significant lower weight gain in the intervention group. The research group followed on and posited that development of further elements to combine with the self-help manual should consider beliefs students hold regarding weight gain prevention behaviours and weight related constructs. This research aimed to investigate the beliefs of first year female students from three universities in the Western Cape, South Africa regarding weight gain prevention behaviours and weight related constructs. The first objective was to elicit salient beliefs held by first year female students regarding weight gain prevention behaviours (dietary patterns, physical activity alcohol intake and sleep time) and weight related constructs (eating behaviour, body shape dissatisfaction, stress, selfesteem and depression/anxiety) using a qualitative research design (Phase 1). The second objective was to identify weight gain prevention belief patterns of first year female students, to investigate the association thereof with actual weight gain prevention behaviours and weight related constructs and identify significant predictors of the belief patterns using a quantitative cross-sectional research design (Phase 2). Methods and results The target population for both Phases was English speaking 18-20-year old first year female students who were registered for the first time for a qualification at University of Cape Town (UCT), Stellenbosch University (SU) or the University of the Western Cape (UWC) in South Africa. Students who were pregnant, breastfeeding, elite athletes, following dietary restrictions for a medical condition, or had a disease that may influence their weight, were not eligible for participation. For Phase 1 total of 28 in-depth interviews were conducted with participants with representation of living situation (university residence or private accommodation, those living at home were excluded) and race (black African, mixed ancestry or white) ensured in recruitment. Eighteen of the interviews were fully coded until data saturation was apparent. The additional 10 interviews were coded for new information only. Data analysis was conducted using the audio coding option on Nvivo Version 12. Core belief themes that emerged reflect awareness of recommendations of behaviours of weight gain prevention, awareness of benefits of performance of these behaviours, awareness of consequences of not meeting the requirements as well as non-concern relating to not performing the behaviours. Further beliefs focused mainly on barriers to and facilitators these behaviours. Phase 2 comprised completion of a questionnaire that covered socio-demographics, self-reported weight and height, dietary (including alcohol intake), physical activity, sleep time, body shape satisfaction, eating behaviour, self-esteem, presence of depression/anxiety symptoms and belief statements (derived from Phase 1) by a convenience sample of 168 first year female students from the same three universities to identify weight gain prevention (WGP) belief patterns, associated factors and predictors thereof. Four weight gain belief patterns (WGP Belief Patterns) were extracted using principal component analysis: WGP Belief Pattern 1: Barriers to weight management; WGP Belief Pattern 2: Facilitators for healthy eating and exercise; WGP Belief Pattern 3: Barriers to exercise; WGP Belief Pattern 4: Social barriers to healthy eating. Numerous associations between these belief patterns and dietary patterns including snacking after dinner, problematic eating behaviours (including a higher emotional eating, cognitive restraint and uncontrolled eating), body shape dissatisfaction, attempts to prevent weight gain during the study year, a higher or lower BMI, perception of overweight/obesity as a child/adolescent, higher stress and lower self- esteem were evident. Regression analysis identified identified snacking after dinner, emotional eating, body shape dissatisfaction and attempts to prevent weight gain during the study year as predictors of a higher score, whereas a higher BMI and perception to have been thin as an adolescent as predictors of a lower score on WGB Belief Pattern 1; for WGP Belief Pattern 2: a higher BMI and a higher score for Dietary Pattern 2 (fruits, vegetables and legumes) were identified as predictors of a higher score, and a higher MET-minutes and a higher score for Dietary Pattern 1 (sugary foods/drinks, slap chips, take-outs) as predictors of a lower score; for WGP Belief Pattern 3: a higher BMI and uncontrolled eating were identified as being predictors of a higher score, and a higher self-esteem and weight gain prevention attempts in the study year as predictors of a lower score; and a higher level of body shape dissatisfaction and a higher level of cognitive restraint were identified as being predictors of a higher score, and a higher BMI, perception of being thin as a child, lower stress and a higher self-esteem as predictors of a lower score on WGP belief pattern 4. Overarching conclusions Results and conclusions of the in depth interviews conducted to assess the beliefs of first year female students from three universities in the Western Cape, South Africa, regarding weight gain prevention behaviours and weight related constructs show that a multicultural sample of students held numerous beliefs regarding potential barriers and facilitators to weight gain prevention. Results of the quantitative assessment of these beliefs in a cross-sectional survey conducted amongst the same target group resulted in the extraction of three barrier WGP Belief Patterns, including barriers to weight management per se (feeling stressed/anxious or sad/depressed, mindless eating, being awake at night, experiencing lack of health food options at university, preparing one's own meals, feeling fat, having people around you who do not eat healthy and the difficulty of not overeating were barriers to weight management), barriers to exercise (feeling sad/depressed, feeling stressed/anxious, having poor body shape satisfaction and feeling fat were barriers to exercise) and social barriers to healthy eating (socialising, judgement from peers when making healthy food choices and drinking alcohol were barriers to weight management). Specific predictors of these patterns, namely snacking patterns, cognitive restraint, uncontrolled eating, emotional eating, problematic eating behaviours, body shape dissatisfaction, overweight/obesity as a child/adolescent, higher stress levels and lower self-esteem have typically been reported to be associated with challenges to healthy weight management. A concern is that students who participated in the cross sectional survey were characterized by many of these predictors. Predictors of the single facilitator WGP Belief Pattern (facilitators of healthy eating and exercise: complying with a healthy diet plan, finding enjoyment in healthy eating, preparing vegetables in a tasty way, finding affordable ways to eat healthy, making time in the day for exercise, knowing how to prepare one's own meals, planning meals and snacks ahead and exercising) that was extracted from the quantitative data reflect factors that have typically been reported to be associated with improved weight management (healthy eating and higher physical activity levels), as well as factors that have typically been reported to be associated with weight management challenges (unhealthy eating and a higher BMI). Overarching recommendations Although the associations between the four weight gain prevention belief patterns and weight status of first year female students were not investigated in this study, factors found to be associated with and predictors of the three barrier patterns point to potential risk for the experience of weight gain prevention challenges by first year female students. Although this notion should ideally be confirmed in further research, addressing the focus of the beliefs included in the barrier belief patterns, as well as the characteristics of the students that have been reported to be associated with weight management challenges in the literature in weight gain prevention interventions for first year female students at tertiary institutions is recommended.